The use of video modeling during distance learning to acquire an interrogative word for female students with intellectual disability - Al-Awwad, Rawan Saleh; Al-Suhaibani, Jana Omar (Journal of Curriculum and Teaching Methodology, 2022)
The study aims to identify the effectiveness of using video modeling during learning education in acquiring and maintenance an interrogative word for schoolgirls with intellectual disabilities, and then generalizing them. It was conducted by using an experimental curriculum that was represented by Single Subject Design. The study sample consists of three students with intellectual disabilities who are enrolled in schools including intellectual education classes. They are in the third intermediate grade. The results indicate the effectiveness of involving video modeling during distance education. Thus, they can obtain the interrogative word with a 100% successful rate. Moreover, they retain them with full percentage points and so were able to generalize them at a rate ranging between 67%-100%. The two researchers concluded that the use of video modeling as a strategy during distance learning has shown positive results, due to exposing the students to sensory stimuli. Also, the short video time, and its continuous repetition has contributed to attracting the attention of female students throughout the sessions.
Keywords: Intellectual Disability; Distance Learning; Video